Segmenting and classifying MRI images for brain tumors using CNN - Sharma, Niharika; Mishra, Prakhar; Sadhana, K; Nithyakani, P (International Journal of Engineering and Technology, 2018)
Gliomas are one of the most prevalent and aggressive form of brain tumours in the world. Patient's usually go on to live a very short life after the initial diagnosis. Therefore, it is crucial to successfully and quickly outline a method for diagnosing the same in it's very earliest stages.Magnetic Resonance Imaging, or MRI as it is more frequently called is a noninvasive method of imaging parts of human anatomy. MRI's utilise robust fields of magnetism, along with waves that have frequencies corresponding to the radio waves in the spectrum to develop precise pictures to get a sense of the happenings inside the human body. The current, most widely used method of diagnosis for brain gliomas involves an oncologist or radiologist reading the MRI image and using his knowledge and experience regarding the same to reach a diagnosis. However, this manual method of diagnosis is very tedious and has been prone to errors in the past. Therefore, it essential to develop an automatic method for the same.Most of the techniques used currently for segmenting brain tumours were initially developed for other diseases, the most common use among them being the separation of white matter lesions. Most of the current methodologies can be broadly categorised into two families- 1.General Probabilistic Methods- Probabilistic methods are a remarkable method to establish the validity of combinatorial entities with distinct characteristics. Although the basis of their existence lies in probability, they are not bounded by it and can be used to solve and evaluate theorems across different branches of Mathematics.2.Discriminative Approaches- They are also sometimes referred to as Conditional Models. We utilise CNN's for faster and accurate processing of the data.Â Â